Love & death in Renaissance Italy - Cohen, Thomas V. (Thomas Vance), 1942- (University of Chicago Press, 2004)
Offering a colourful portrait of Renaissance Rome, Thomas Cohen has trawled the remarkable court archives in the city to produce six sordid tales of adultery, violence, conspiracy, greed & murder as they were presented before the magistrates.